Pancasila sebagai Soft Power Diplomasi Indonesia dalam Forum Hukum Internasional (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This study discusses the role of Pancasila as the foundational and ideological basis of the Indonesian state in the context of international diplomacy, as well as its implications for the formation of national law and foreign policy. Pancasila functions not only as a normative foundation but also as a form of soft power that supports Indonesia's position in the global arena. This research uses a qualitative method with a literature study approach, drawing from journals, books, and relevant legal documents. The findings indicate that Pancasila influences Indonesia’s foreign diplomacy through core values such as social justice, deliberation, and humanity. However, challenges remain in its implementation, particularly in maintaining consistency between Pancasila’s values and global as well as national interests. In the context of international law, Pancasila as a legal ideal (rechtsidee) contributes to the development of a just, inclusive, and tolerant legal system. Therefore, revitalizing the understanding of Pancasila is crucial to ensure it remains a central guideline in every foreign policy decision and national legal development in Indonesia.